2022
DOI: 10.1186/s13071-022-05548-5
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of Clonorchis sinensis and hepatitis B virus: clinical liver indices and interaction in hepatic cell models

Abstract: Background In China, people infected with hepatitis B virus (HBV) are commonly found in areas with a high prevalence of Clonorchis sinensis, a trematode worm. Published studies have reported that the progression of hepatitis B is affected by coinfection C. sinensis. Methods Clinical data from a total of 72 patients with C. sinensis and HBV (as sole infection or with coinfections) and 29 healthy individuals were analysed. We also incubated the hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It has been observed that patients co-infected with C. sinensis and HBV exhibit higher levels of serum HBV DNA than patients infected with HBV alone [28,29]. Clinical data have demonstrated that patients with co-infection of C. sinensis and HBV have signi cantly elevated levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TB), and hyaluronic acid (HA) compare to those with HBV infection alone [30]. A survey conducted in the high incidence area of clonorchiasis in the Lalin River, Northeast China, reported that out of 854 cases of clonorchiasis, 46 cases were co-infected with HBV (HBsAg positive).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that patients co-infected with C. sinensis and HBV exhibit higher levels of serum HBV DNA than patients infected with HBV alone [28,29]. Clinical data have demonstrated that patients with co-infection of C. sinensis and HBV have signi cantly elevated levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TB), and hyaluronic acid (HA) compare to those with HBV infection alone [30]. A survey conducted in the high incidence area of clonorchiasis in the Lalin River, Northeast China, reported that out of 854 cases of clonorchiasis, 46 cases were co-infected with HBV (HBsAg positive).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have revealed that coinfection of C. sinensis and HBV can promote liver brosis and chronic in ammation. Co-stimulation of the hepatic stellate cell line LX-2 with the total proteins from C.sinensis adult worms (CsTPs) and HBV positive serum leads to increased transcription of alpha-smooth muscle actin and types I and III collagen, as well as pro-in ammatory cytokines TNF-α, IL-1β, and IL-6 [30]. Recent studies have highlighted the ability of parasite extracellular vesicles (EVs) to mediate the host competing endogenous RNA (ceRNA) regulatory network across species through their own non-coding RNA (ncRNA) with regulatory function [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, concurrent infections with HBV and HCV in trematode endemic areas are often observed (Abruzzi et al, 2016;Gao et al, 2020). Related to increased Th2 cytokines, patients with concurrent helminth and HBV or HCV infection showed increased viral replication and liver fibrosis (Abruzzi et al, 2016;Li et al, 2016;Dong et al, 2022). Hence, chronic inflammatory processes associated with hepatic viral replication next to Th2-mediated fibrotic responses to Schistosome eggs may result in more extensive liver damage caused mainly by immune-mediated mechanisms (Shin et al, 2016).…”
Section: Sths and Hepatotropic Virusesmentioning
confidence: 99%
“…One study confirmed that C . sinensis could aggravate the progression of liver fibrosis [ 15 ]. Our study demonstrated that C .…”
Section: Introductionmentioning
confidence: 99%